Violence and Political Struggle. A Study of their Repercussions in the Urban Setting through the Case of Cuenca (15th Century) - José María SÁNCHEZ BENITO (Studia Historica. Historia Medieval, 2013)
This paper aims to contribute to the study of violence, its nature and characteristics, as related to the struggle for power during the Late Middle Ages. To achieve this contribution a case study is investigated, its various forms are differentiated, and endpoints that attempt to cover the phenomenon as widely as possible are proposed. Such endpoints range from actors playing a leading role in the facts studied to violence extent and impact on the lives of people.